Syntactical Analysis on Subject and Verb Usage in Descriptive Writing of Eighth grade Students at SMP Bhinneka Nusantara Batam - Shalehoddin Shalehoddin; 2Setia Roulina (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2018)
This research is to find out Subject and Verb are used in descriptive writing and to find out the students percentages of mistakes in using Subject and Verb in Descriptive Writing The research was conducted in three month starting from observing the sample to making report. This research was held on eighth grade students of SMP Bhineka Nusantara Batam. The research method used qualitative methodology. The subject of the research is Smp Bhineka Nusantara Batam. There are several techniques to collect the data that was used in conducting a research, namely observation, questionnaire, interview, and test. In this research, the researcher used test. Technique of analyzing data: measuring the students’ individual mastery, measuring the mean (average) of students’ mastery, measuring the classical mastery.the researcher classified the students’ syntactical analysis in Descriptive writing. Then the researcher only focused on 2 areas: Sentence Pattern (subject and verb) divided by two sentences exactly nominal sentence and verbal sentence. The average of totally non-syntactically is 39 from nominal and verbal (Subject and Verb), while nominal got 54, and verbal got 22 totally, we take all total nominal and verbal are 78 from 30 students